(untitled) (Bioresearch Communications, 2025)
Background: Psychiatric disorders, especially depression and anxiety, are exponentially increasing in post-industrial society. Antibiotic exposure may partly be attributable to the development of such psychiatric disorders. This review study aimed to summarize and explore the associations between antibiotic exposure and human psychiatric disorders, scrutinize the research gaps, and contemplate future research perspectives. This study also identified the reasons for antibiotic misuse and possible prevention and management strategies. Methods: PubMed, Scopus databases, and Google Scholar search engines were searched for relevant articles using the exposure keywords “antibiotic exposure” and outcome keywords “psychiatric disorder” and associated medical subheading terms (MeSH). Human epidemiological studies were retrieved irrespective of age, race, country, and publication year up to August 2024. Finally, 15 articles that fulfilled our inclusion criteria were selected and summarized in the present review. Results: This review summarized all associations between antibiotic exposure and psychiatric disorders along with potent confounders. Most of the studies found a positive association between antibiotic exposure and psychiatric disorders, especially with depression and anxiety, even after adjustment for major lifestyle and demographic factors. The associations might depend on gender, age, antibiotic types, and type of bacterial infections. The magnitude of these associations was higher for higher doses, more frequent uses, and recent uses of antibiotics. Conclusions: Our summarized pieces of evidence indicate that antibiotic exposure might be associated with depression and anxiety in humans. However, a nationwide prospective cohort using human biomonitoring data of antibiotics is warranted to explore the overall scenario in the future. Bioresearch Commu. 11(2): 1881-1889, 2025 (July)